-(6w+v)-4(v-3w)=

Simple and best practice solution for -(6w+v)-4(v-3w)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6w+v)-4(v-3w)= equation:


Simplifying
-1(6w + v) + -4(v + -3w) = 0

Reorder the terms:
-1(v + 6w) + -4(v + -3w) = 0
(v * -1 + 6w * -1) + -4(v + -3w) = 0
(-1v + -6w) + -4(v + -3w) = 0
-1v + -6w + (v * -4 + -3w * -4) = 0
-1v + -6w + (-4v + 12w) = 0

Reorder the terms:
-1v + -4v + -6w + 12w = 0

Combine like terms: -1v + -4v = -5v
-5v + -6w + 12w = 0

Combine like terms: -6w + 12w = 6w
-5v + 6w = 0

Solving
-5v + 6w = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6w' to each side of the equation.
-5v + 6w + -6w = 0 + -6w

Combine like terms: 6w + -6w = 0
-5v + 0 = 0 + -6w
-5v = 0 + -6w
Remove the zero:
-5v = -6w

Divide each side by '-5'.
v = 1.2w

Simplifying
v = 1.2w

See similar equations:

| 7x+3=5x+19 | | 10/40-20/x | | 8/15=n/6 | | x=y/4(21-z) | | 1.25x+6=.62x | | 4/x=26 | | 17+.13x=.17x | | (2x-8)(2x+8)=55 | | 51.98+.17x=55.98+.13x | | 15+.09x=10+.13x | | 6y+13=61 | | 24vx^4+12v^6w^2x=0 | | 1quatre=3 | | 3t+2x=11 | | 10(2x-5)-6= | | 0.775= | | 8(6-k)+5=-5(k-2)-5 | | ((3+8)/(9-3))/(5/6)+(4/5) | | 9.8m-20=-2m | | 11t-10=4t-5 | | 9.8m+20=2m | | 9.8m-10=m*5 | | 9.8-10=m*5m | | 9.8-10=m*5 | | 4u^2-6=5u | | 12x-8=4x+3 | | 9.8m-20=2m | | 3x+x=540 | | x^2+11x=15 | | 3x+y=540 | | 54-4x=23x+24 | | -103-7x=10+16 |

Equations solver categories